Defining the role of efflux pump inhibitors on anti-TB drugs in Rifampicin resistant clinical Mycobacterium Tuberculosis isolates - Pule, Caroline (Stellenbosch : Stellenbosch University, 2014)
Thesis (MScMedSc)--Stellenbosch University, 2014.